Solving dynamics problems in MATLAB - Harper, Brian D. (John Wiley & Sons, 2002)
Over the past 50 years, Meriam & Kraige's Engineering Mechanics: Dynamics has established a highly respected tradition of Excellence—A Tradition that emphasizes accuracy, rigor, clarity, and applications. Now completely revised, redesigned, and modernized, the new fifth edition of this classic text builds on these strengths, adding new problems and a more accessible, student-friendly presentation.